Belief about Nicotine Modulates Subjective Craving and Insula Activity in Deprived Smokers - Gu, Xiaosi; Lohrenz, Terry; Salas, Ramiro; Baldwin, Philip R.; Soltani, Alireza; Kirk, Ulrich; Cinciripini, Paul M.; Montague, P. Read (Frontiers in Psychiatry, 2016)
Little is known about the specific neural mechanisms through which cognitive factors influence craving and associated brain responses, despite of the initial success of cognitive therapies in treating drug addiction. In this study, we investigated how cognitive factors such as beliefs influence subjective craving and neural activities in nicotine-addicted individuals using model-based functional magnetic resonance imaging (fMRI) and neuropharmacology. Deprived smokers (N=24) participated in a two-by-two balanced placebo design which crossed beliefs about nicotine (told “nicotine” vs. told “no nicotine”) with the nicotine content in a cigarette (nicotine vs. placebo) which participants smoked immediately before performing an fMRI task of reward learning. Subjects’ reported craving was measured both before smoking and after the fMRI session. We found that first, in the presence of nicotine, smokers demonstrated significantly reduced craving after smoking when told “nicotine in cigarette” but showed no change in craving when told “no nicotine”. Second, neural activity in the insular cortex related to craving was only significant when smokers were told “nicotine” but not when told “no nicotine”. Both effects were absent in the placebo condition. Third, insula activation related to computational learning signals was modulated by belief about nicotine regardless of nicotine’s presence. These results suggest that belief about nicotine has a strong impact on subjective craving and insula responses related to both craving and learning in deprived smokers, providing insights into the complex nature of belief-drug interactions.